2019
DOI: 10.21203/rs.2.12451/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of Pasteurella multocida isolated from dead rabbits with respiratory disease in Fujian, China

Abstract: Background Pasteurella multocida is one of the important pathogens infects rabbits, causing major economic losses in commercial rabbit farming. In this study, 205 P. multocida isolates recovered from lungs of dead rabbits with respiratory disease were defined capsular serogroups, lipopolysaccharide (LPS) genotypes and multi-locus sequence types, screened virulence factors, and tested antimicrobial susceptibility. Results The 205 isolates were assigned into 2 capsular types, A and D, and 2 LPS genotypes, L3 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Fujian Province, in the southeast of China, is one of the important rabbit-farming areas in China [13]. The number of live rabbits farmed was about 9.4 million by the end of 2018 (Fujian Statistical Yearbook, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Fujian Province, in the southeast of China, is one of the important rabbit-farming areas in China [13]. The number of live rabbits farmed was about 9.4 million by the end of 2018 (Fujian Statistical Yearbook, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For penicillins , one study from Egypt reported that all of 10 included isolates were resistant to both ampicillin (included as a surrogate for penicillin/amoxicillin, used only by the parenteral route in rabbits) and amoxicillin–clavulanic acid (Awad and Abd El‐Hamid, 2019). Another study from Brazil (Ferreira et al, 2012) found 10.9% and 6.5% of 45 isolates resistant to penicillin and amoxicillin, respectively, whereas a Chinese study found all 205 included isolates susceptible to penicillin (Wang et al, 2019). All isolates from the Brazilian and Chinese studies were susceptible to fluoroquinolones (enrofloxacin), whereas 1% of isolates from the French surveillance system were resistant to this drug (RESAPATH, 2020).…”
Section: Assessmentmentioning
confidence: 99%
“…bronchiseptica spreads rapidly in rabbits and the infection is often persistent, causing economic losses to the rabbit farming [9]. Fujian Province, in the southeast of China, is one of the important rabbit farming areas in China [10]. To the best of our knowledge, B. bronchiseptica is a common pathogen isolated from rabbits with respiratory disease in Fujian Province.…”
mentioning
confidence: 99%